Primary central nervous system lymphoma: a real-world comparison of therapy access and outcomes by hospital setting. Issue 3 (12th January 2022) - Patel, Akshat M; Ali, Omer; Kainthla, Radhika; Rizvi, Syed M; Awan, Farrukh T; Patel, Toral; Pan, Edward; Maher, Elizabeth; Desai, Neil B; Timmerman, Robert; Kumar, Kiran A; Ramakrishnan Geethakumari, Praveen
Abstract: Background: This study analyzes sociodemographic barriers for primary CNS lymphoma (PCNSL) treatment and outcomes at a public safety-net hospital versus a private tertiary academic institution. We hypothesized that these barriers would lead to access disparities and poorer outcomes in the safety-net population. Methods: We reviewed records of PCNSL patients from 2007–2020 ( n = 95) at a public safety-net hospital ( n = 33) and a private academic center ( n = 62) staffed by the same university. Demographics, treatment patterns, and outcomes were analyzed. Results: Patients at the safety-net hospital were significantly younger, more commonly Black or Hispanic, and had a higher prevalence of HIV/AIDS. They were significantly less likely to receive induction chemotherapy (67% vs 86%, P = .003) or consolidation autologous stem cell transplantation (0% vs. 47%, P = .001), but received more whole-brain radiation therapy (35% vs 16%, P = .001). Younger age and receiving any consolidation therapy were associated with improved progression-free (PFS, P = .001) and overall survival (OS, P = .001). Hospital location had no statistical impact on PFS ( P = .725) or OS ( P = .226) on an age-adjusted analysis. Conclusions: Our study shows significant differences in treatment patterns for PCNSL between a public safety-net hospital and an academic cancer center. A significant survival difference was not demonstrated, which is likely multifactorial, but likely was positively impacted by the shared multidisciplinary care delivery between the institutions. As personalized therapies for PCNSL are being developed, equitable access including clinical trials should be advocated for resource-limited settings.